A content analysis on the portrayal of romantic love and relationships in OPM music videos featured in MYX daily top 10 pinoy charts - Pobadora, Lemuel G. (2018)
This thesis is a content analysis that looked into the portrayal of romantic love in OPM music videos featured in Myx Daily top 10 Pinoy Charts from the months of December 2017 to February 2018. There were 20 music videos analyzed for the study, all of which were gathered from Myx?s online charts archive. It was found that majority of the sample music videos visually portrayed romantic relationships. The researcher then looked into how the stages of romantic relationships were portrayed in the music videos and which stages were the most frequent. Cultural love styles were also analyzed for how they applied in the narratives of the music videos. The study found that all music videos among the samples that portrayed romantic love and relationships portrayed the early stages of romantic relationships. It was also found that the music videos put some emphasis on familiarity, stability, and passion between two people in a relationship. The researcher concluded that the music videos from Myx generally used visual images and narratives that were familiar for Filipino audiences based on literature that showed how Filipino viewed romantic love and relationships.